Corrigendum - United Nations (Law of the Sea Bulletin, 2014)
On page 18, the footnote should instead read: “Note by the Editor: The list of geographical coordinates of points, specifying the geodetic data were deposited with the Secretary-General under articles 76(9) and 84 of the Convention (see Maritime Zone Notification M.Z.N.92.2012.LOS of 9 November 2012).”